Sickness absence and relative income - Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2018)
We analyse labour supply and absence from work choices, assuming that individual preferences exhibit relative consumption concerns. We show that contractual hours and the length of absence periods may vary equally with the strength of positional considerations. In this case, positional concerns do not affect their difference, i.e. overall or effective working time. Moreover, the nature and intensity of relative consumption effects influence the impact of sick pay and of true illness periods on contractual work hours and absence behaviour. Consequently, the profitability of employing individuals also varies with the strength of their positional concerns.
Keywords: D62; H53; I18; J22; J32; 330; Absence; Labour Supply; Positional Concerns; Relative Consumption; Sick Pay